Santri Resilience: Uncovering Santri Coping Strategies in Dealing with Friendship Issues - Seviyeni; Hasibuan, Adelia Pertiwi (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to explore the coping strategies of Islamic boarding school students in dealing with friendship problems that often arise in Islamic boarding schools. The primary focus of this study is to analyze the extent of resilience of Islamic boarding school students through their coping strategies in dealing with friendship problems and how this affects their success in living their daily lives and their achievement in memorizing the Qur’an. This study employs a qualitative case study approach to examine the coping strategies and resilience of Islamic boarding school students in addressing friendship problems. The results of this study indicate that the students’ resilience in dealing with friendship problems is at a reasonable level. This is evidenced by the students’ ability to manage social and emotional stress by increasing self-awareness in viewing each problem as a learning process, focusing on long-term goals, and through self-reflection and spirituality. This study shows that the coping strategies implemented by Islamic boarding school students play an important role in building resilience to deal with friendship problems, especially in the Islamic boarding school environment. Increased self-awareness, social support, focus on long-term goals, and self-reflection and spirituality have proven to be key factors in helping students manage social and emotional stress.